Rapid reporting self assessment cd-rom - Dick, E. A. (London : Remedica Publishing, 2000)
Featuring 10 packets of rapid reporting films, each packet containing 30 single films
North Thames Part 2B FRCR
System requirements: Microsoft Windows 486/50 MHz or higher, 8 MB RAM (5 MB available) with Windows 3.1; or Pentium with 16 MB (10 MB available) with Windows 95/NT. CD ROM drive (quad speed recommended)
Apple Macintosh 33 MHz, 8 MB RAM (5 MB available) with System 7.1 or higher; or powerPC, 16 MB RAM (8 MB available) with System 7.5 or higher. CD ROM drive (quad speed recommended)
Keywords: Radiography, Medical; Radiology -- education; Technology, Radiologic